2018
DOI: 10.1002/jum.14683
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of 1‐ and 3.2‐MHz Low‐Intensity Pulsed Ultrasound on Osteogenesis on Porous Titanium Alloy Scaffolds: An In Vitro and In Vivo Study

Abstract: Under the present experimental conditions, LIPUS promoted osteoblast differentiation and promoted bone maturity on porous Ti64 scaffolds. No significant differences were noted between the two frequencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…The LIPUS used in our study provided an option for mechanical force loading on the piezoelectric materials that is not yet documented in the literature even though it has been approved by the U.S. FDA for the treatment of fresh fractures and existing non-union fractures. The parameters we applied were screened in earlier stages of research and were confirmed through both in vivo and in vitro biological experiments to promote osteogenesis in MC3T3-E1 cells [ [25] , [26] , [27] ]. Those parameters can be changed, allowing tissue-specific physiological demands to be fulfilled.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The LIPUS used in our study provided an option for mechanical force loading on the piezoelectric materials that is not yet documented in the literature even though it has been approved by the U.S. FDA for the treatment of fresh fractures and existing non-union fractures. The parameters we applied were screened in earlier stages of research and were confirmed through both in vivo and in vitro biological experiments to promote osteogenesis in MC3T3-E1 cells [ [25] , [26] , [27] ]. Those parameters can be changed, allowing tissue-specific physiological demands to be fulfilled.…”
Section: Discussionmentioning
confidence: 99%
“…The sham group was treated likewise with the ultrasound generator turned off. These parameters were selected based on previous findings by our group [ [25] , [26] , [27] ].
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…Alkaline Phosphatase (ALP) Activity. ALP is an indicator of osteogenic differentiation, bone formation, and matrix mineralization [13]. The activity of ALP was detected to analyze the differentiation of MC3T3-E1 cells on ZSM-5/Ti-2448 and Ti-2448.…”
Section: Cell Proliferation and Cytotoxicitymentioning
confidence: 99%
“…Low-intensity pulsed ultrasound (LIPUS) is a nonthermal and noninvasive technique that utilizes physical stimulation by acoustic pulsed energy [3]. This is frequently used for the treatment of fresh fractures or delayed healing of fractures because it shortens the time required for biological wound healing.…”
Section: Introductionmentioning
confidence: 99%